The agricultural economy of Thailand - Sabatini, Omero ([Washington] U.S. Dept. of Agriculture, Economic Research Service, 1972)
This report reviews the rapid expansion and diversification of Thailand's agricultural production and trade and surveys prospects of its farm trade with the United States and the rest of the world, as of mid 1971
Cover title.
Bibliography: p. 96-99.
osc 30/01/2019
Loans
Keywords: Agriculture; Agriculture and state